1994
DOI: 10.1097/00007632-199410150-00010
|View full text |Cite
|
Sign up to set email alerts
|

▪ Transverse Atlantal Ligament Disruption Associated with Odontoid Fractures

Abstract: Osteoperiosteal ligamentous avulsion injuries were identified on MR imaging in three patients and were associated with acute and delayed instability and nonunion. The combination of MR imaging, CT, and plain radiographs is useful in evaluating unstable odontoid fractures to facilitate rational treatment planning. Odontoid fractures with transverse ligament injuries should be considered for early surgical stabilization because this combination of injuries is unlikely to heal nonoperatively. Anterior odontoid sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…Neurologic injury, if present, usually results in catastrophic or fatal consequences due to the high level of spinal cord involved. Concomitant spinal injuries are present in up to 34% of patients; 85% occurring in the cervical spine, with the atlas most commonly affected [5][6][7][8]. The number of associated injuries is significantly more common in younger patients.…”
Section: Introductionmentioning
confidence: 99%
“…Neurologic injury, if present, usually results in catastrophic or fatal consequences due to the high level of spinal cord involved. Concomitant spinal injuries are present in up to 34% of patients; 85% occurring in the cervical spine, with the atlas most commonly affected [5][6][7][8]. The number of associated injuries is significantly more common in younger patients.…”
Section: Introductionmentioning
confidence: 99%
“…6 Ruptures of the cruciate ligament can be further classified as ligamentous disruption versus avulsion of the atlantal tubercle. 11,12,24 During in vitro testing, the cruciate ligament was found to be so taut that catastrophic failure occurs upon any tear, described as the "all or none" phenomenon. 10,12,31 Failure of the tectorial membrane has also been associated with flexion in front-end motor vehicle collisions 35 and may lead to dural tears, as the superior-most aspect is continuous with the dura.…”
Section: Biomechanics Of Simple Cvj Pathologymentioning
confidence: 99%
“…20 In cases of Type II odontoid fracture, instability will persist even after successful bone fusion is achieved. 24 Therefore, disruption of the TAL is a contraindication for anterior screw fixation for odontoid fractures. The incidence of concomitant TAL disruption and odontoid fracture is low.…”
Section: Incompetence Of the Talmentioning
confidence: 99%
“…The incidence of concomitant TAL disruption and odontoid fracture is low. In a study of 30 patients with odontoid fractures, Greene et al 24 reported a 10% incidence of TAL injury and advocated the use of MR imaging to assess TAL integrity as a part of the initial evaluation of all odontoid fractures. In a study of 77 patients with odontoid fractures, however, Sayama et al 51 reported no cases of atlantoaxial instability, and these authors recommended MR imaging screening only if patients present with neurological deficits or widening of the atlantodental interval greater than 3 mm on radiographs or CT scans.…”
Section: Incompetence Of the Talmentioning
confidence: 99%